Risk Factors for Inpatient Hypoglycemia in a Tertiary Care Hospital in Indonesia - Pratiwi, Chici; Martin Rumende; Kshanti , Ida Ayu Made; Soewondo, Pradana (Journal of the ASEAN Federation of Endocrine Societies, 2022)
Introduction. Hypoglycemia is an important and harmful complication that often occurs in inpatient and outpatient settings. This study aims to assess the incidence of inpatient hypoglycemia and its related factors. We also assessed mortality and length of hospital stay. Methodology. We performed a retrospective cohort study among patients with type 2 diabetes mellitus admitted to a tertiary hospital in Indonesia. Using multivariate regression, we analyzed age, sex, body mass index, comorbidities, history of hypoglycemia, hyperglycemia treatment administered, nutritional intake, and medical instruction as the related risk factors for inpatient hypoglycemia. Results. From 475 subjects, 80 (16.8%) had inpatient hypoglycemia, of which, 7.4% experienced severe hypoglycemia. We found that patients with a history of hypoglycemia (RR: 4.6; 95% CI: 2.8-7.6), insulin and/or sulfonylurea treatment (RR 6.4; 95% CI: 1.6-26.5), and inadequate nutritional intake (RR 2.6; 95% CI: 1.5-4.3) were more likely to have hypoglycemic events compared to those who did not. The length of hospital stay for patients in the hypoglycemic group is significantly longer than those in the non-hypoglycemic group (13 vs 7 days, p<0.001), but their mortality rates did not differ (16% vs 10.9%, p=0.18). Conclusion. Inpatient hypoglycemia may be affected by a history of hypoglycemia and inadequate nutritional intake. Patients who had inpatient hypoglycemia tend to have a longer median length of hospital stay.